THE SHRINKING HYPOTHALAMIC LESION: SERIAL MRI-GUIDED MANAGEMENT OF REFRACTORY XANTHOMATOUS HYPOPHYSITIS - Chin , Yik Hin; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Xanthomatous hypophysitis is a rare inflammatory condition affecting the pituitary gland, characterized by the presence of lipid-laden macrophages (xanthoma cells) and chronic inflammation. CASE We describe a 26-year-old female with a 12-year history of xanthomatous hypophysitis complicated by panhypopituitarism and diabetes insipidus. Initial presentation at age 13 years with growth failure led to transcranial tumor debulking in 2016, with histopathology confirming chronic xanthogranulomatous inflammation. Due to recurrent disease activity, she received two courses of high-dose prednisolone (2018 and 2019–2020), followed by maintenance azathioprine (initiated 2020, currently 25 mg daily). Serial MRI surveillance showed a gradual regression of the lesion over time. In July 2023, the hypothalamic lesion measured 1.3 × 0.8 × 0.8 cm, a reduction from its previous size of 1.5 × 1.3 × 1.1 cm in 2021. This regression was accompanied by decreased compression on the optic chiasm. The pituitary gland remained thinned, and the posterior pituitary bright spot is absent, consistent with long-standing structural damage. These findings suggest ongoing inflammatory control under azathioprine. Hormonal management included levothyroxine (37.5 mcg/day), sublingual desmopressin (60 mcg/day for DI), and cyclic estrogen-progestin (Progyluton). Adrenal function recovered post-steroid withdrawal, confirmed by a normal Synacthen test (peak cortisol 624 nmol/L, 2022). Complications included secondary osteoporosis (spine T-score -1.8, hip -2.5) managed with calcium/vitamin D, and microcytic anemia (Hb 9.4 g/dL, MCV 29.8 fL), likely due to iron deficiency, now treated with oral iron and folate. CONCLUSION This case highlights the chronic relapsing-remitting nature of xanthomatous hypophysitis, necessitating long-term immunosuppression and meticulous endocrine surveillance. The latest MRI findings (2023) confirm disease stability under azathioprine, supporting its role in preventing progression. However, residual hypothalamic involvement underscores the need for continued monitoring. A multidisciplinary approach (endocrinology, neurosurgery, rheumatology) remains essential to manage hormonal deficits, bone health, and potential disease recurrence. Future considerations include azathioprine tapering if imaging remains stable, emphasizing the importance of serial MRI in guiding therapy.